IMPACT DE LA ROUTE BITUMÉE BONDOUKOU-BOUNA SUR L’INSTABILITÉ DES COMMUNAUTÉS PAYSANNES AU NORD-EST DE LA CÔTE D’IVOIRE: LE CAS DES PAYSANS LOBI - Joseph, Kra Kouadio; Koissy, Koffi Yéboué Stéphane (European Scientific Journal, ESJ, 2013)
This article deals with the issue of the instability of Lobi peasants in the north-east of Côte d'Ivoire. This problem has been delt with the colonial and post-colonial administration unsuccessfully. But since the opening of the Bondoukou-Bouna tarred road which is 166 kilometers long in 1997, deep changes have occurred in the Lobi peasants commutement. It is about their progressive stabilization. The cultural commutement realities are becoming an obstacle and as a result it is developing into an economic and commercial situation. They are no more moving or commuting. This sedentarization about the tarred road takes part in the transformation of the agricultural space, food security and the emergence of developing large market towns.